Bariatric surgery in solid organ transplant patients: Long‐term follow‐up results of outcome, safety, and effect on immunosuppression. Issue 11 (14th April 2018) - Yemini, Renana; Nesher, Eviatar; Winkler, Janos; Carmeli, Idan; Azran, Carmil; Ben David, Matan; Mor, Eytan; Keidar, Andrei
Abstract : The surgical risk of transplanted patients is high, and the modified gastrointestinal anatomy after bariatric surgery (BS) may lead to pharmacokinetic alterations in the absorption of immunosuppressive drugs. Data on outcomes of BS and the safety and feasibility of maintaining immunosuppression and graft safety among solid organ transplanted patients are scarce. In the current study, weight loss, improvement in comorbidities, and changes in dosage and trough levels of immunosuppression drugs before and after BS were analyzed for all transplanted patients who underwent laparoscopic sleeve gastrectomy (LSG) or laparoscopic Roux‐en‐Y gastric bypass (LRYGB) in our institution between November 2011 and January 2017. Thirty‐four patients (13 females, 21 males, average age 53 years) were included in the study. A successful weight loss (>50% excess weight loss in 28 of them [82%]) was recorded at the last follow‐up. Comorbidities improved significantly. Immunosuppressive stability increased from 39% to 47% among all patients. The tacrolimus blood trough levels declined slightly, but remained within therapeutic range. These data suggest that LSG and LRYGB ensure good immunosuppressive maintenance together with significant weight loss and improvement in comorbidities without serious graft rejection or dysfunction. The surgical risk is higher than in the regular BS population. Abstract : This study of 34 transplanted patients who underwent bariatric surgery shows that there is good immunosuppressive maintenance together with significant weight loss and improvement in comorbidities without serious graft rejection or dysfunction.